A 60 GHz Planar Diplexer Based on Substrate Integrated Waveguide Technology. (27th February 2013) - Athanasopoulos, Nikolaos; Makris, Dimitrios; Voudouris, Konstantinos
Abstract : This paper presents a millimeter-wave, 60 GHz frequency band planar diplexer based on substrate integrated waveguide (SIW) technology. Diplexer consists of a pair of 5th-order SIW bandpass channel filters with center frequencies at 59.8 GHz and 62.2 GHz providing 1.67% and 1.6% relative bandwidths, respectively. SIW-to-microstrip transitions at diplexer ports enable integration in a millimeter-wave transceiver front end. Measurements are in good agreement with electromagnetic simulation, reporting very good channel isolation, small return losses, and moderate insertion losses in the passbands. The proposed SIW planar diplexer is integrated into a millimeter-wave transceiver front end for 60 GHz point-to-point multigigabit wireless backhaul applications, providing high isolation between transmit and receive channels.